2016
DOI: 10.14210/rtva.v18n3.p584-610
|View full text |Cite
|
Sign up to set email alerts
|

Experiência turística memorável, percepção cognitiva, reputação e lealdade ao destino: um modelo empírico

Abstract: Os destinos, de acordo com mudanças de comportamento dos turistas, começam a se posicionar como fornecedores de experiências. Neste contexto, estudos recentes apontam que as experiências turísticas relevantes tendem a aumentar a propensão dos turistas de se lembrarem do destino. O objetivo principal deste estudo foi propor e testar um modelo de relações entre as dimensões subjacentes da Experiência Turística Memorável, da Percepção Cognitiva, da Reputação e da Lealdade ao Destino. A metodologia foi um survey c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
15

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 13 publications
0
12
0
15
Order By: Relevance
“…Kotler and Armstrong (1999) emphasize the importance of maintaining relationships in business, considering that the purpose is to create a long-term link between the parties. The authors affirm, however, that it is important to create value for both companies and customers, thus fostering customer satisfaction and the company's likely success in marketing its products/ services and, consequently, in achieving customer loyalty (Aroeira, Dantas & Gosling, 2016). For Peppers and Rogers (1997), the market has undergone a great evolution over time, with different and more demanding consumers, forcing organizations to become aware that quality of service is a minimum requirement to be competitive in the market, and it is also visible that relational proximity is a distinguishing factor, and consequently can be a condition for an organization's success.…”
Section: Literature Review: Relationship Marketingmentioning
confidence: 85%
“…Kotler and Armstrong (1999) emphasize the importance of maintaining relationships in business, considering that the purpose is to create a long-term link between the parties. The authors affirm, however, that it is important to create value for both companies and customers, thus fostering customer satisfaction and the company's likely success in marketing its products/ services and, consequently, in achieving customer loyalty (Aroeira, Dantas & Gosling, 2016). For Peppers and Rogers (1997), the market has undergone a great evolution over time, with different and more demanding consumers, forcing organizations to become aware that quality of service is a minimum requirement to be competitive in the market, and it is also visible that relational proximity is a distinguishing factor, and consequently can be a condition for an organization's success.…”
Section: Literature Review: Relationship Marketingmentioning
confidence: 85%
“…In the Brazilian context, Aroeira et al (2016) point out that hedonism, involvement, novelty, local culture and knowledge, and refreshment are dimensions of the MTE. Thus, the proposed scale from the studies of Kim et al (2012) demonstrated a fusion of the local culture dimension with the knowledge dimension, and meaningfulness was not considered significant in the Brazilian study.…”
Section: Memorable Tourism Experience (Mte)mentioning
confidence: 99%
“…For the author, MTEs relates to tourists' experiences with the environment, culture, interpersonal relationships and psychological perceptions. Besides, part of the scale, which included the dimensions Hedonism, Refreshment, Meaningfulness, and Involvement, had already been translated from the studies of Kim et al (2012) and tested in the national context by Aroeira et al (2016). A part of the items of the culture and novelty scales was translated by Aroeira et al (2016), and other items were proposed and tested by Coelho (2017) A 7-point Likert scale anchored all items.…”
Section: Instrumentmentioning
confidence: 99%
See 2 more Smart Citations